Hybridization of practices in teacher–researcher collaboration. (January 2018) - Hamza, Karim; Palm, Ola; Palmqvist, Jenny; Piqueras, Jesús; Wickman, Per-Olof
In this paper we present experiences from a joint collaborative research project which may be described as an encounter between a school science teaching practice and a university science didactics research practice. We provide narratives which demonstrate how the encounter between these two communities of practice interacted to produce hybridization between the two in terms of mutual influences, resulting in the conceptual and practical development of both communities of practice. We argue that what happened in the project suggests one way of reducing the gap between educational research and teaching through the emergence of practices where the roles of teachers and researchers become blurred.